Organizational Moralities and Social Transition: Towards a Conceptualization of Organizational Regulation in a Transitional Age - Lippens, R. (Journal of business ethics, 2001)
This essay attempts to think through the impact of what we call our "transitional age" on organizational life, specifically on organizational regulation, and thus on organizational moral life. It provides notes towards a reconceptualization of organizational moral life that may be helpful to all students and practitioners of organization and business ethics who would want to make sense of the often significant contextuality, unpredictability, and undecidability of contemporary organizational life.